Lyfjameðferð kransæðasjúklinga á Íslandi - Emil L. Sigurðsson; Jón Steinar Jónsson; Guðmundur Þorgeirsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: During the last decades the knowledge of prevention of coronary heart disease (CHD) has increased dramatically. Results from large clinical trials on drug treatment of patients with CHD with various groups of drugs has given new possibilities to improve the prognosis of our patients. However, results from several studies have shown that this knowledge has not yet been put into practice. The main aim of our study, which is a part of a larger enquiry into the actual practice of secondary prevention of CHD in Iceland, was to evaluate the medical treatment of CHD, other than lipid lowering therapy. Material and methods: All patients with residence in Hafnarfjörður, Garðabær and Bessastaðahreppur who have been diagnosed as having CHD were sent a letter with an invitation to participate in the study and a request for an informed consent. Those who choose to participate responded to a questionnaire and gave a permission for a review of their records with respect to a specific diagnosis and lipid values. The patients were divided into four groups on the basis of their history: I. myocardial infarction (MI), II. coronary artery bypass surgery (CABG), III. percutaneous transiluminal coronary angioplasty (PTCA) and IV. angina pectoris (AP). If a patient fulfilled the critera for more than one diagnostic group the CABG group had the highest priority followed by PTCA, MI and finally AP. Results: A total of 533 patients with CHD were living in the study area and of those 402 (75%) participated in the study. Aspirin was used by 284 patients (71%), 75% among men and 65% among women (p=0.018). The highest proportion (91%) being among those who had undergone CABG, and the lowest among those with angina pectoris (56%). Half of the patients (52%) used beta blockers and 119 (30%) diuretics. A total of 172 patients received treatment with nitrates (43%), 57% of the women and 27% of the men (p=0.006). Calcium blockers were ...